THE ROLE OF LEADERSHIP STYLES IN CLASSROOM MANAGEMENT - Tiur Simanjuntak (Politeknik Negeri Sriwijaya, 2009)
Being a teacher in a classroom needs knowledge not only in terms of the knowledge of the subject itself but also in term of knowing how to handle the class such as leadership skill because this skill is able to maintain students spirit or morale also requires skill so that the students have self confident to speak English without being afraid of making mistakes and being laughed by their friends. The aim of this paper is to analyze leadership styles available and to find out an appropriate style that can be applied in an English classroom. Several types ranged from an authorization style to democratic to laissez faire have been viewed and analyzed. An autocratic is one in which the manager retains the decision making rights to herself, it is task oriented, it gives orders to subordinates, and the type of communication is one-way downwards. In contrast, in a laissez-faire decision style, the manager imposes few, if any, controls on subordinates. Decisions are left to subordinates and it is they who are the principle initiators of actions. In English class room the situation of learning a foreign language has been discussed. Some principles required by a foreign language have been mentioned. The situation required by a foreign language classroom should be relax and able to encourage students to talk or communicate using the target language. Besides the situation, learners should also be taken into consideration. The way to behave to one student as individuals is different to another. It is mostly influenced by the maturity task owned by a student and a class. By looking at the advantages and disadvantages of two extreme styles, it is suggested that there is no best style in leadership. The best is the leadership which considers situation that can build up good relationship between leader and followers.